Molecular Associations and Clinical Significance of RAPs in Hepatocellular Carcinoma - Kumari, Sarita; Arora, Mohit; Singh, Jay; Kadian, Lokesh K.; Yadav, Rajni; Chauhan, Shyam S.; Chopra, Anita (Frontiers in Molecular Biosciences, 2021)
Hepatocellular carcinoma (HCC) is an aggressive gastrointestinal malignancy with a high rate of mortality. Multiple studies have individually recognized members of RAP gene family as critical regulators of tumor progression in several cancers, including hepatocellular carcinoma. These studies suffer numerous limitations including a small sample size and lack of analysis of various clinicopathological and molecular features. In the current study, we utilized authoritative multi-omics databases to determine the association of RAP gene family expression and detailed molecular and clinicopathological features in hepatocellular carcinoma (HCC). All five RAP genes were observed to harbour dysregulated expression in HCC compared to normal liver tissues. RAP2A exhibited strongest ability to differentiate tumors from the normal tissues. RAP2A expression was associated with progressive tumor grade, TP53 and CTNNB1 mutation status. Additionally, Rap2a expression was associated with the alteration of its copy numbers and DNA methylation. Rap2a also emerged as an independent marker for patient prognosis. Further, pathway analysis revealed that RAP2A expression is correlated with tumor-infiltrating immune cell composition and oncogenic molecular pathways, such as cell cycle and cellular metabolism.